2008
DOI: 10.1890/08-0299.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploitative Competition Between Invasive Herbivores Benefits a Native Host Plant

Abstract: Abstract. Although biological invasions are of considerable concern to ecologists, relatively little attention has been paid to the potential for and consequences of indirect interactions between invasive species. Such interactions are generally thought to enhance invasives' spread and impact (i.e., the ''invasional meltdown'' hypothesis); however, exotic species might also act indirectly to slow the spread or blunt the impact of other invasives. On the east coast of the United States, the invasive hemlock woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 31 publications
(37 reference statements)
0
34
0
Order By: Relevance
“…This study suggests that alien herbivorous insects can indirectly exert both top-down and bottom-up impacts on native fauna. Preisser and Elkinton (2008) documented competitive interactions between two alien insect specialists of hemlock: hemlock woolly adelgid and elongate hemlock scale (Fiorinia externa Ferris). The densities of both species were reduced by 30% in mixed-species relative to single-species trials.…”
Section: Impacts On Native Faunamentioning
confidence: 99%
“…This study suggests that alien herbivorous insects can indirectly exert both top-down and bottom-up impacts on native fauna. Preisser and Elkinton (2008) documented competitive interactions between two alien insect specialists of hemlock: hemlock woolly adelgid and elongate hemlock scale (Fiorinia externa Ferris). The densities of both species were reduced by 30% in mixed-species relative to single-species trials.…”
Section: Impacts On Native Faunamentioning
confidence: 99%
“…A second invasive herbivore, the elongate hemlock scale (Fiorinia externa; EHS), also feeds on eastern hemlocks in North America (McClure, 1977). Although both species are sapsucking insects that are considered pests, they have different impacts on their shared host (Preisser and Elkinton, 2008). In a multi-year experiment, Miller-Pierce et al (2010) found that infestation with HWA, but not EHS, significantly decreased tree growth.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of multiple invaders in an ecosystem may change interaction outcomes which would occur between one invader and native species (Preisser and Elkinton 2008). Several studies so far have demonstrated different interaction outcomes that might arise from the presence of multiple invaders, which range from negative (e.g.…”
Section: Introductionmentioning
confidence: 99%